Genome-Wide Marker Data-Based Comparative Population Analysis of Szeklers From Korond, Transylvania, and From Transylvania Living Non-Szekler Hungarians - Ádám, Valerián; Bánfai, Zsolt; Sümegi, Katalin; Büki, Gergely; Szabó, András; Magyari, Lili; Miseta, Attila; Kásler, Miklós; Melegh, Béla (Frontiers in genetics, 2022)
Genome-wide genotype data from 48 carefully selected population samples of Transylvania-living Szeklers and non-Szekler Hungarians were analyzed by comparative analysis. Our analyses involved contemporary Hungarians living in Hungary, other Europeans, and Eurasian samples counting 530 individuals altogether. The source of the Szekler samples was the commune of Korond, Transylvania. The analyzed non-Szekler Hungarian samples were collected from villages with a history dating back to the era of the Árpád Dynasty. Population structure by principal component analysis and ancestry analysis also revealed a great within-group similarity of the analyzed Szeklers and non-Szekler Transylvanian Hungarians. These groups also showed similar genetic patterns with each other. Haplotype analyses using identity-by-descent segment discovering tools showed that average pairwise identity-by-descent sharing is similar in the investigated populations, but the Korond Szekler samples had higher average sharing with the Hungarians from Hungary than non-Szekler Transylvanian Hungarians. Average sharing results showed that both groups are isolated compared to other Europeans, and pointed out that the non-Szekler Transylvanian Hungarian inhabitants of the investigated Árpád Age villages are more isolated than investigated Szeklers from Korond. This was confirmed by our autozygosity analysis as well. Identity-by-descent segment analyses and 4-population tests also confirmed that these Hungarian-speaking Transylvanian ethnic groups are strongly related to Hungarians living in Hungary.